The estimate of convergence rate in the min-schema of multivariate random variables - Jokimaitis, Arvydas (Lietuvos matematikos rinkinys, 1998)
In this paper the nonuniform estimate of the convergence rate for the distribution of the minima of multivariate random variable is obtained.